The effectiveness of Norwegian capital controls - Willem Jos Jansen; Günther G. Schulze (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
The Norwegian capital controls had a significant effect on stock returns only in the early eighties when controls were stringent although they did not influence short-term interest rates throughout the sample period (1980-90). Our result thus contributes to a growing body of evidence on the ineffectiveness of capital controls in developed economies. Apart from evasion through international trade (leading and lagging, misinvoicing), the dichotomous structure of the Norwegian economy and of the controls offered arbitrage possibilities. A dominant outward oriented oil sector was banned from the domestic capital market and referred to international markets while the case was reversed for the rest of the economy. Linkages between offshore and mainland economy prevented the control system from working.
Keywords: F21; F31; F32; F36; 330